1994
DOI: 10.21273/jashs.119.5.1068
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to Fusarium oxysporum at Different Developmental Stages of Asiatic Hybrid Lilies

Abstract: Tests for determining resistance to Fusarium oxysporum f.sp. lilii in different developmental stages of Lilium were developed. Under standardized conditions, commercial bulbs, yearling bulbs, scale bulblets, and scales of 16 Asiatic lily cultivars were tested for Fusarium resistance. Disease ratings were analyzed statistically using a threshold model for ordered categorical data. For each cultiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Breeding for resistance of lily is limited by the relative long juvenile phase, the relative slow propagation of clones and the lack of reliable screening assays during this phase. Screening tests at clonal level have been developed for Fusarium in lily (Straathof and Löffler, 1994a), however, these tests can only be performed several years after crossing and need retesting. Straathof and L öffler (1994b) showed that several genes are involved in the resistance mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Breeding for resistance of lily is limited by the relative long juvenile phase, the relative slow propagation of clones and the lack of reliable screening assays during this phase. Screening tests at clonal level have been developed for Fusarium in lily (Straathof and Löffler, 1994a), however, these tests can only be performed several years after crossing and need retesting. Straathof and L öffler (1994b) showed that several genes are involved in the resistance mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…This could be due to differences in developmental stage or to the quality of the bulbs. Differences due to the developmental stage is unlikely as demonstrated by Straathof & Loffler (1994) in Asiatic hybrids. The (inner) quality of the bulbs, however, may be variable.…”
Section: Discussionmentioning
confidence: 99%
“…Bulb observations were carried out 8 wk (scale bulblets) or 20 wk (yearling bulbs) after planting (Straathof & Loffler, 1994). The resistance levels of genotypes were measured using a disease rating.…”
Section: Screening Assaymentioning
confidence: 99%
“…lilii is the main pathogen that causes lily basal rot. 2 F. oxysporum can survive for a long time as mycelium in the bulbs or as mycelium, chlamydospore, or sclerotium with diseased residue in the soil. At present, chemical control methods are the main measures to prevent and control lily basal rot.…”
Section: Introductionmentioning
confidence: 99%
“…4 Although the germplasm resources of Lilium species resistant to F. oxysporum have been used in disease-resistant breeding, the molecular mechanism of disease resistance is rarely reported. In 2013, a cDNA library of the root of F. oxysporuminfested Lilium regale was constructed by suppression subtractive hybridization and 180 sequences homologous to known Transcriptome Sequencing Analysis Provides Insights Into the Response to Fusarium oxysporum in Lilium pumilum 2…”
Section: Introductionmentioning
confidence: 99%